The Socialist Peopled Libyan Arab Jamahiriya : 2003 Article IV Consultation-Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2003)
The Libyan economy remains saddled with extensive controls, restrictions, and subsidies that continue to distort prices and resource allocations, hinder efficiency and competitiveness, and impede the performance of the economy. Executive Directors commended the liberalizing of the economy, and stressed the need to improve macroeconomic management, remove trade restrictions, accelerate structural reforms, and tighten monetary and fiscal policies. They supported the authorities' request for technical assistance from the IMF in the areas of statistics, financial programming, development of money markets, and financial instruments, and tax reform.